2002
DOI: 10.1177/1077727x02030004004
|View full text |Cite
|
Sign up to set email alerts
|

Financial Ratio Analysis of Korean Households

Abstract: The purpose of this study is to explore the usefulness and limitations of six family financial ratio guidelines developed in the United States in assessing the financial situation of households in South Korea. The ratios examined are debt safety, debt service, solvency, liquidity, savings, and capital accumulation. Guidelines for the first three ratios tend to be enforced by lenders and have similar patterns in both countries, but Korean households are much more likely to meet savings and liquidity guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Kim and Lyons (2008) also controlled for income and wealth when using the solvency, liquidity, and investment asset ratio and noted that not meeting the investment guidelines used in the study was associated with lower levels of income and wealth for all three ratios. Moon, Yuh, and Hanna (2002) were able to calculate the inflection point on income when each ratio changed from positive to negative. Using a liquidity guideline of three months, they found that income had a positive effect on the liquidity ratio up to $50,966, but above this amount until $87,616, it had a negative effect.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Kim and Lyons (2008) also controlled for income and wealth when using the solvency, liquidity, and investment asset ratio and noted that not meeting the investment guidelines used in the study was associated with lower levels of income and wealth for all three ratios. Moon, Yuh, and Hanna (2002) were able to calculate the inflection point on income when each ratio changed from positive to negative. Using a liquidity guideline of three months, they found that income had a positive effect on the liquidity ratio up to $50,966, but above this amount until $87,616, it had a negative effect.…”
Section: Independent Variablesmentioning
confidence: 99%
“…The capital accumulation ratio reveals how well an individual or family is advancing toward financial goals for capital accumulation. It compares the value of investment assets with net worth (Moon, et al 2002, p. 501).…”
Section: Capital Accumulation Ratiomentioning
confidence: 99%
“…However, the above definitions all emphasize the ability to satisfy current and future needs of household members and to ward off sudden deterioration of their financial situation. Likewise, there are no generally accepted standards for the measurement of financial security (Kochis 1996), except the one typically used in the related area, namely the financial status of individuals or households in terms of their financial resources relative to current and future financial needs (Hacker 2011;Greninger et al, 1996;Moon et al, 2002).…”
Section: Introduction 11 Household Financial Securitymentioning
confidence: 99%